Technology acceptance model to analyze factors influencing intention to use bitcoin in Algerian context - TROUDI, Hadjer; BENFARES, Amani (Journal of Human Sciences, 2025)
The purpose of this paper is firstly to support the adaptability of technology acceptance model in Algerian context and secondly to explore drivers of behavioral intention to adopt bitcoin. A framework based on TAM was proposed in order to explore intention to use bitcoin. The sample collected combines students from Constantine 2 compus and Constantine adherents of Algerian bitcoins’ forum, for data analysis structural equation modeling approach was established via Amos 24 software. The findings show that construct was good model fit and can be applied to explain theory since the model was confirmed. Results indicate that intention to use bitcoin by Algerian user is mostly influenced by subjective norm contrarily to government regulation that shows a non-negative and a non-significant effect, intention is impacted by attitude which is affected positively by perceived usefulness and perceived ease to use, and negatively by compatibility. study gives better understanding for practitioners and researchers in practical way the importance level of several influencing factors studied that need to be considered for individual aging category 20-30 having knowledge about crypto-currencies in Algerian context.